Production and characterization of bacterial cellulose synthesized by Enterobacter chuandaensis strain AEC using Phoenix dactylifera and Musa acuminata - AL-Hasabe, Ashraf Sami Hassan; Abdull Razis, Ahmad Faizal; Baharum, Nadiya Akmal; Yu, Choo Yee; Mat Isa, Nurulfiza (Springer Science and Business Media Deutschland GmbH, 2024)
Bacterial cellulose (BC) is a biopolymer synthesized extracellularly by certain bacteria through the polymerization of glucose monomers. This study aimed to produce BC using Enterobacter chuandaensis with fruit extracts from Phoenix dactylifera (D) and Musa acuminata (M) as carbon sources. Attenuated Total Reflectance-Fourier Transform Infrared Spectroscopy (ATR-FTIR) showed characteristic cellulose vibrations, while X-ray diffraction (XRD) identified distinct peaks at 15.34°, 19.98°, 22.58°, and 34.6°, confirming the cellulose structure. Whole-genome sequencing of E. chuandaensis identified key genes involved in BC production. The BC produced then exhibited a molecular weight of 1,857,804 g/mol, with yields of 2.8 g/L and 2.5 g/L for treatments D and M, respectively. The crystallinity index of the purified BC was 74.1, and 13C NMR analysis confirmed the dominant cellulose Iα crystalline form. The BC showed high biocompatibility in cytotoxicity assays, with cell viability between 92% and 100%, indicating its potential for use in biomedical applications. This investigation represents the first report of BC production by E. chuandaensis, which promises a new avenue for sustainable and efficient BC synthesis using fruit extracts as carbon sources. © The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature 2024.